The Tourist Demand from the Perspective of Motivation and Satisfaction around Gastronomy: The Case of Olón, Ecuador - VILLAGÓMEZ-BUELE, César; CARVACHE-FRANCO, Mauricio; CARVACHE-FRANCO, Orly; CARVACHE-FRANCO, Wilmer; RAMÓN-CASAL, Tito; HOLGUÍN-IBARRA, Irene (Journal of Environmental Management and Tourism, 2022)
Gastronomy has become a determining factor in the development of many tourist destinations; hence, its motivations greatly influence on satisfaction. This study will determine the satisfaction of diners through the offer segmented according to the preferences of food consumption. The empirical study was carried out in Olón, which is part of The Spondylus route that runs from south to north the Ecuadorian coast, where tourist attractions of sun and beach are appreciated. This study aims to investigate the tourist demand, through a mixed methodology, using interviews and surveys, to understand the gastronomic tourism reality of the location, and present an intellectual contribution that serves as the basis for future research. Among the most outstanding results, it was observed that large groups of families and friends visited the beach during weekends, with the intention of trying local foods to satisfy their trip. As Gastronomic Tourism grows, it is important to understand the tourist motivations and satisfaction to improve each segment service offering. This research shows original results of the motivation and satisfaction of the demand for gastronomic tourism, based in the commune of Olón that crosses the Spondylus Route in Ecuador. According to visitors, the hospitality and quality of the dishes were of vital importance, and both the ceviche and the seafood rice proved to be indispensable dishes. Finally, the satisfaction of the demand for gastronomy reached a medium-high acceptance, which represents opportunities to improve the visitor experience.